2018
DOI: 10.1002/ajpa.23643
|View full text |Cite
|
Sign up to set email alerts
|

Transhumance pastoralism of Roccapelago (Modena, Italy) early‐modern individuals: Inferences from Sr isotopes of hair strands

Abstract: The variable modern human hair Sr/ Sr ratios show that high-resolution hair sampling tracks the movements of this individual between the two continents. The Sr isotope composition of the mummy hair is consistent with sub-annual human movements from Roccapelago to an area with different Sr/ Sr ratios. Historical sources indicate that individuals from Roccapelago travelled with their herds to Tuscany for transhumance pastoralism practices. The high radiogenic Sr/ Sr ratios (>0.71) found in some of the hair are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…δ 15 N hair values vary with the rate and type of animal-protein consumed, with significantly higher values for Canadians who frequently eat seafood ( Fig 3 ) and significantly lower values in ovo-lacto vegetarians relative to the rest of the population ( Table 4 ). This finding reinforces previous studies that showed the importance of seafood consumption on δ 15 N hair variability at the individual [ 32 ] and at the population scale [see review in 10 ]. However, when including seafood and meat consumption as predictors in a multivariate regression model, those variables explain only a negligible portion of the δ 15 N hair variance in the Canadian population ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…δ 15 N hair values vary with the rate and type of animal-protein consumed, with significantly higher values for Canadians who frequently eat seafood ( Fig 3 ) and significantly lower values in ovo-lacto vegetarians relative to the rest of the population ( Table 4 ). This finding reinforces previous studies that showed the importance of seafood consumption on δ 15 N hair variability at the individual [ 32 ] and at the population scale [see review in 10 ]. However, when including seafood and meat consumption as predictors in a multivariate regression model, those variables explain only a negligible portion of the δ 15 N hair variance in the Canadian population ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…Keratinized tissues, hairs and nails, are an ideal substrate for analyzing δ 13 C, δ 15 N and δ 34 S values in dietary studies, as these elements are abundant in keratin and record dietary isotopic values chronologically as they grow [4][5][6][7]. Isotope data from hair can thus provide snapshots of the diet from an individual or population at a monthly temporal resolution [8][9][10][11][12]. Stable isotope variations in hair have been particularly successful in demonstrating dietary transition in human populations by tracing, for example, the progressive increase in processed food products in certain indigenous community diets [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the potential of using 87 Sr/ 86 Sr ratios in keratinous tissues to identify local versus non-local signal for humans (Font et al, 2012;Vautour et al, 2015), to identify migration paths and breeding sites for birds (Font et al, 2007), and to reconstruct travel history of horses (Chau et al, 2017). The 87 Sr/ 86 Sr ratios in hair samples may also be used in archeological studies to identify the travel history of buried human remains (Frei et al, 2015(Frei et al, , 2017Lugli et al, 2018). Similarly, the provenance of ancient textiles could be identified using strontium isotope analysis in wool (Frei et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Strontium isotopes are widely used by the geochemical community and applied in several different research fields, such as petrology, archaeology, palaeontology, palaeoclimatology, stratigraphy, forensics and food traceability (Kelly et al , Zhou et al , McArthur et al , Kimura et al , Durante et al , Lin et al , Bolea‐Fernandez et al , Willmes et al , Lugli et al , , Weber et al ). However, for the application of radiogenic Sr isotopes to carbonate samples, the availability of suitable microanalytical reference materials (MRMs) for in situ analyses is limited.…”
mentioning
confidence: 99%